Evaluación de perfiles fermentativos para la elaboración de cerveza artesanal por levaduras nativas (2019)
The consumption of artisanal beers is growing stronger. The market faces a consumer who wants new experiences and flavours than those traditionally offered by the brewing industry, is of interest the search for new raw materials (malts) and even fermenting micro-organisms which may offer other organoleptic characteristics, from this, it was carried out the isolation and study of yeasts that could offer other sensory characteristics to the traditional ale beer of one of the main artisan brewery of Bogotá. The isolations were concentrated in native yeasts, which are responsible for metabolising the sugars contained in the must to convert them into ethanol. For this, three ripe fruits (passion fruit, plum and guava) were selected which had a high microbiota content, which was isolated in selective media for eukaryotes, then a selection of yeast strains was made, which differed in Saccharomyces and No Saccharomyces, in lysine agar and later, in Sabouraud agar with cyclohexifenide (antibiotic). Finally, API 20C AUX tests were applied to determine the yeast genus, where the isolation of strains corresponding to the genus Candida tropicalis was obtained as a result.